El alumno como parte activa en el proceso de enseñanza /aprendizaje de inglés para fines específicos - NAVARRO COY, Marta (Didáctica. Lengua y Literatura, 2010)
Learning autonomy has, over the past few decades, become quite a current issue in education mainly as a result of the significance progressively being awarded to the actual individual doing the learning. Accordingly, we have a great base of literature at our disposal that manifests the importance of raising awareness in the learners of how essential it is for them to become the people with the most say in their learning process. This awareness-raising and the learners’ putting this management role into practice can and should begin in the classroom with the appropriate guidance, when required, of the teacher. Along these lines, this paper attempts to reflect, contrary to what is generally assumed, that the student in the language classroom actually is capable of demonstrating a great willingness and interest to become involved in the decision-making process that influences his/her own learning so much.